Malta : Financial Sector Assessment Program-Technical Note-Risk Analysis. (IMF Staff Country Reports; Country Report, 2019)
This technical note presents Malta's risk analysis related aspects of financial system. A comprehensive set of stress tests and interconnectedness analyses were conducted to assess the resilience of Malta's financial system and shed light on potential vulnerabilities, complementing the euro area Financial Sector Assessment Program. Key metrics suggest that the banking sector is in good health, but challenges exist. Banks are well-capitalized, liquidity is ample, and profitability has been healthy. The solvency stress tests indicate that the banking sector remains resilient, with vulnerabilities limited to a few small banks. The banking sector appears resilient to liquidity pressures, but some small banks are vulnerable to more severe events. The interconnectedness analysis suggests that contagion risk through interlinkages from within the Maltese financial sector is currently higher and more wide-spread than contagion risk through cross-border interbank exposures. Monitoring and conducting periodic analysis of cross-border linkages, and further enhancing the existing inter-sectoral linkages analysis, is expected to provide an early warning before contagion risks accumulate.